ANALISIS EFISIENSI PENYALURAN AIR IRIGASI DENGAN SISTEM INFORMASI GEOGRAFIS BENDUNGAN LOMAYA KABUPATEN BONE BOLANGO PROVINSI GORONTALO - Yurizal Biahimo; David Rumambi; Daniel Ludong; Sandra Pakasi (Universitas Sam Ratulangi, 2015)
ABSTRACT Bone Bolango district of Gorontalo province is well developed in agriculture. There are three dams in this province and one of them is Lomaya dam. This dam has not yet used technology of geographic information system for evaluating the efficiency of water distribution in the irrigated area. Therefore the measurement of water discharge and the information of spatial irrigated areas are required. The inflow and outflow discharges were measured in each irrigated channel using a bottle buoy. The result of the research showed that the efficiencies of primary, secondary and tertiary channels were 82,25 %, 78,58 % and 77,99 % respectively.The total efficiency of water distribution of irrigated area in Lomaya was 50,41 %. Geographic information system in these irrigated area of Lomaya served the map of irrigated area. Keywords: Efficiency, Irrigation, Geographic Information System, Dam Lomaya